Electrode for water electrolysis and method of manufacturing the same

Electrodeposition of a Ni-Sn-Fe or Ni-Sn-Co composite film on a conductive base material forms a dendritic or columnar structure with directly bonded double hydroxides, addressing the challenges of non-noble metal electrodes by enhancing catalytic activity and durability in water electrolysis.

JP2025004692AActive Publication Date: 2025-01-15YAMAGUCHI PREFECTURAL INDAL TECH INST
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023104551
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-06-26
Publication Date
2025-01-15
Estimated Expiration
2043-06-26

AI Technical Summary

Technical Problem

Existing water electrolysis electrodes, particularly those using non-noble metals, face challenges in achieving high catalytic activity and durability due to issues such as insufficient activity, peeling, and decreased conductivity when using polymer binders, and the formation of dense double hydroxides at low current densities.

Method used

A method involving electrodeposition of a composite film comprising Ni, Sn, and optionally Fe or Co on a conductive base material, forming a dendritic or columnar structure with a double hydroxide directly bonded to the surface, without using polymer binders, at high current densities to enhance electron transfer efficiency.

Benefits of technology

The resulting electrodes exhibit high catalytic activity and durability, maintaining performance over extended periods with improved electron transfer efficiency and reduced material and manufacturing costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025004692000001_ABST
    Figure 2025004692000001_ABST
Patent Text Reader

Abstract

To provide an electrode for water electrolysis that has high catalytic activity and is highly durable enough to maintain the high catalytic activity for a long time and a method of manufacturing the same, with respect to water electrolysis reaction employing a non-noble metal electrode which may be a substitute for a noble metal electrode, and is low in material / manufacturing cost.SOLUTION: An electrode for water electrolysis is an electrode used for electrolytic manufacture of hydrogen etc., through electrolysis of water, and also formed by directly bonding together a first deposit having Ni combined with Sn and Fe with a surface of a conductive base material and a second deposit as a compound oxide with a surface of the first deposit.SELECTED DRAWING: Figure 7
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an electrode used for electrolytic production of hydrogen and the like by electrolysis of water, and more particularly to a water electrolysis electrode made of a non-noble metal and having high catalytic activity and high durability, and a method for producing the same. [Background technology]

[0002] Today, as the depletion of fossil fuels becomes a problem, there is an urgent need to find clean and sustainable alternative energy sources. One solution to this problem is the realization of a hydrogen carrier society. In a hydrogen carrier society, hydrogen that does not emit CO2 (carbon dioxide) is produced through water electrolysis, and when energy is needed, this hydrogen can be converted into energy using fuel cells or other devices. In other words, hydrogen itself becomes a new energy medium. In order to build this hydrogen carrier society that can move away from a carbon society, efforts are currently being made around the world to reduce the production costs of hydrogen fuel. In particular, improving the performance of the electrodes used in water electrolysis is considered to be a key technology for reducing hydrogen production costs.

[0003] Currently, the basic hydrogen strategy presented by the government to realize a hydrogen carrier society aims to set the unit cost of hydrogen production at 20 yen / [Nm 3 The goal is to keep the cost of hydrogen production below 600 [mA / cm]. The cost of hydrogen production takes into account the equipment costs, maintenance costs, and labor costs for operating the water electrolysis device, but electricity costs are considered to be the largest contributor. To produce hydrogen as cheaply as possible, the question is how to reduce the electricity costs required to cause the water electrolysis reaction, and so improving the functionality of electrodes such as those in this invention is considered important. The New Energy and Industrial Technology Development Organization (NEDO), a national research and development agency, is working on a cell current density of 600 [mA / cm] for water electrolysis. 2 The goal is to build a cell with an electrolysis voltage of 1.8 V or less, and electrodes are being developed with this value as the target.

[0004] In particular, the bottlenecks in improving the performance of water electrolysis are the hydrogen evolution reaction that takes place at the cathode of the water electrolysis device and the oxygen evolution reaction (OER) that takes place at the anode. Both reactions are multi-step reactions and are known to have inherently slow reaction rates, but since the OER in particular involves four proton-coupled electron transfers, there is a demand for high efficiency anodes. Due to these issues, the current situation is that electrodes based on precious metals such as Pt (platinum), Ru (ruthenium) and Ir (iridium)-based oxides are used for commercial water electrolysis. However, these electrodes have disadvantages such as high cost, rarity and low durability, which significantly limit their large-scale use. Therefore, non-precious metals such as Ni (nickel) and Co (cobalt) have been widely used as inexpensive catalytic metals. Patent Document 1 discloses an invention called "soluble electrode catalyst" that relates to a non-precious metal Ni-Sn composite film in which Ni is combined with Sn (tin). In this invention, + +2e - =H2), Sn selectively dissolves during electrolysis, and as the electrolysis time increases, the surface area of ​​the electrode increases, and activity is maintained. Other examples include oxides and hydroxides of Ni, Fe (iron) and Co, and double hydroxides having a structure such as LDH (layered double hydroxide). For example, Non-Patent Document 1 discloses a technique in which Nafion is used as a polymer binder, mixed with a catalyst, and then evaluated as an electrode. Furthermore, as a method for directly bonding a substrate and a double hydroxide or a double hydroxide itself without using a polymer binder, there is an electrodeposition method. For example, Non-Patent Documents 2 to 4 disclose that a current density of 20 [mA / cm 2 ] is used in a bath containing Ni, Sn, and Fe precursors. 2 In addition, Non-Patent Document 5 discloses a technique for synthesizing a catalyst at a current density of 50 [mA / cm 2 in a bath containing precursors of Ni, Sn, and Co. 2] discloses a technique for synthesizing a catalyst. Furthermore, Non-Patent Document 6 discloses a technique for synthesizing a catalyst at different electrodeposition potentials (−0.70 V to 0.90 V vs. SCE (Saturated Calomel Electrode)). [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2013-117041 A [Non-patent literature]

[0006] [Non-Patent Document 1] Facile Synthesis of Nickel-Iron / Nanocarbon Hybrids as Advanced Electrocatalysts for Efficient Water SplittingXing Zhang, Haomin Xu, Xiaoxiao Li, Yanyan Li, Tingbin Yang, and Yongye Liang ACS Catalysis 2016, 6, 580-588. [Non-Patent Document 2] Electrodeposition of self-supported NieFeeSn film on Ni foam: An efficient electrocatalyst for oxygen evolution reactionYihui Wu, Ying Gao, Hanwei He, Ping Zhang Electrochimica Acta 301 (2019) 39-46. [Non-Patent Document 3] Electrodeposition of self-supported Ni-Fe-Sn film on Ni foam: An efficient electrocatalyst for oxygen evolution reaction Ji-Qiong Lian, Yi-Hui Wu, Hou-An Zhang, Si-Yong Gu, Ying Chen, Ji-Dong Ma, Yan-Ling Hu Materials Letters 227(2018)124-127.

Non-Patent Document 4

Non-Patent Document 5

Non-Patent Document 6

[0007] However, in the invention disclosed in Patent Document 1, the oxygen generating reaction (4OH - =2H2O+O2+4e - When the Ni-Sn composite film is used as an anode in the catalytic reaction for hydrogen evolution, the mechanism is different from that of the hydrogen evolution reaction described above, so there was a problem that sufficient activity and durability could not be obtained even when the Ni-Sn composite film was used as an anode. In addition, many of the techniques disclosed in Non-Patent Document 1 and related techniques use pyrolysis or hydrothermal methods, and therefore are synthesized through a multi-step process. In addition, when used as an electrode, it is necessary to mix the obtained powder sample with a polymer binder and apply it to a substrate, which leaves issues such as a decrease in activity due to a decrease in conductivity between catalysts or between the catalyst and the substrate, and a decrease in durability due to physical peeling of the catalyst. Furthermore, even in the techniques disclosed in Non-Patent Documents 2 to 6, when a double hydroxide is synthesized at a low current density range or a low electrodeposition potential on the base side, which is used in conventional synthesis for applications such as corrosion prevention or decoration, the morphology of the precipitate is dense and smooth, and a double hydroxide in a composition range in which activity is functional is not formed. In the present invention, double hydroxides can be deposited in a single step without using a polymer binder by electrodeposition at a high current density in a bath containing a transition metal. The electrode of the present invention has a unique structure in which a double hydroxide is directly bonded to the surface of a dendritic or columnar deposit that is directly bonded to the surface of a substrate. In other words, a double hydroxide having essentially high activity is bonded along the contour of the surface of a dendritic or columnar deposit with a large surface area, providing a water electrolysis electrode in which a synergistic effect of activity and surface area is achieved. The present invention has been made in response to the above-mentioned conventional problems, and aims to provide a water electrolysis electrode that employs a non-precious metal electrode, which is an alternative to precious metal electrodes and has low material and production costs, and that has high catalytic activity and high durability capable of maintaining this high catalytic activity for a long period of time, and a method for producing the same. [Means for solving the problem]

[0008] To achieve the above object, a first aspect of the present invention provides an electrode for water electrolysis, comprising a first precipitate, in which Ni is combined with Sn and Fe, formed on a surface of a conductive base material, and a second precipitate, which is a double hydroxide, directly bonded to the surface of the first precipitate. A double hydroxide is an oxide or hydroxide containing at least Fe, Ni, and Sn, or may contain iron oxyhydroxide (FeOOH) or nickel oxyhydroxide (NiOOH), and may further contain an oxide or hydroxide containing Co.

[0009] The water electrolysis electrode of the second invention is the electrode of the first invention, characterized in that, in a composition of the first precipitate, when the total of Ni, Sn, and Fe is taken as 100 at% (atomic percentage), Sn is 0.8 to 77 at% and an Fe / Ni ratio is in the range of 0.01 to 4 at%.

[0010] The electrode for water electrolysis according to a third invention is the electrode for water electrolysis according to the second invention, characterized in that the second precipitate has a composition in which, when the total of Ni, Sn, Fe and oxygen is taken as 100 at%, Sn is 0.1 to 33 at%, the Fe / Ni ratio is in the range of 9.93 to 49.19 at%, and oxygen is in the range of 5 to 49 at%.

[0011] The water electrolysis electrode according to a fourth aspect of the present invention is characterized in that, in the first aspect of the present invention, Ni is composited with Co in addition to Sn and Fe.

[0012] The water electrolysis electrode of a fifth invention is the electrode of the fourth invention, characterized in that the composition of the first precipitate is such that, when the total of Ni, Sn, Co, and Fe is taken as 100 at%, Sn is in the range of 0.8 to 77 at%, Co is in the range of 0 to 23 at% (excluding 0), and the Fe / Ni ratio is in the range of 0.01 to 4 at%.

[0013] The water electrolysis electrode of a sixth invention is the fifth invention, characterized in that, when the total of Ni, Sn, Co, Fe and oxygen is taken as 100 at%, the composition of the second precipitate is such that Sn is in the range of 0.1 to 33 at%, Co is in the range of 0 to 70 at% (excluding 0), the Fe / Ni ratio is in the range of 9.93 to 49.19 at%, and oxygen is in the range of 5 to 49 at%.

[0014] A seventh aspect of the present invention is an electrode for water electrolysis according to any one of the first to sixth aspects of the present invention, wherein the conductive base material is made of any one of Al, Ni, carbon, Cu, Ti, and stainless steel.

[0015] The electrode for water electrolysis according to an eighth aspect of the present invention is any one of the first to sixth aspects of the present invention, wherein the first precipitate has a dendritic or columnar structure in which columnar secondary arms, which act as branches, grow in irregular directions from a columnar primary arm which serves as a main trunk.

[0016] A method for producing an electrode for water electrolysis according to a ninth aspect of the present invention includes a step of disposing, as a precursor, chloride salts containing at least NiCl2, SnCl2, and FeCl3 on a conductive base material by a wet film-forming method; a first film-forming step of precipitating a first precipitate in which Ni is composited with at least Sn and Fe by the wet film-forming method; and a second film-forming step of directly bonding a second precipitate which is a double hydroxide to a surface of the first precipitate by the wet film-forming method, wherein the temperature of the plating bath in the first and second film-forming steps is 50°C, the pH is 8, and the plating current density is 40 to 2000 mA / cm. 2 The present invention is characterized in that it controls the temperature to be lower than the normal temperature. Effect of the Invention

[0017] In the water electrolysis electrodes according to the first to eighth aspects of the present invention, a first precipitate in which Ni is combined with Sn and Fe is directly bonded to the surface of a conductive base material, and a second precipitate which is a double hydroxide is directly bonded to the surface of the first precipitate. As a result, even a non-precious metal electrode which is inexpensive in terms of material and production costs can exhibit extremely advantageous effects such as high catalytic activity and high durability which enables the high catalytic activity to be maintained for a long period of time. By directly bonding the second precipitate, which is a double hydroxide, to the surface of the first precipitate, optimal electronic structures are formed between the substrate and the catalyst (the first precipitate and the second precipitate), between the catalysts themselves, and between the catalyst and the aqueous solution during the water electrolysis reaction, ensuring excellent performance in terms of activity and durability. In particular, efficient electron transfer between catalysts becomes possible, and even if only the first precipitate or the second precipitate is formed on the conductive substrate, the efficiency of electron transfer is poor because the efficiency depends only on the physical properties of the precipitate. Furthermore, the method for producing an electrode for water electrolysis according to the ninth aspect of the present invention makes it possible to produce a non-precious metal electrode for water electrolysis which has high catalytic activity and durability and is inexpensive in terms of material and production costs. [Brief description of the drawings]

[0018] [Figure 1] FIG. 1 is a flow diagram showing a method for producing a water splitting electrode according to a first embodiment of the present invention. [Figure 2A] FIG. 2 is a schematic diagram illustrating a state after preparation of a plating bath (solution) in the method for producing an electrode for water electrolysis according to the first embodiment. [Figure 2B] FIG. 2 is a schematic diagram showing a first stage of a reaction in a plating bath (solution) in the method for producing a water electrolysis electrode according to the first embodiment. [Figure 2C] FIG. 4 is a schematic diagram showing a second stage of a reaction in a plating bath (solution) in the method for producing a water electrolysis electrode according to the first embodiment. [Figure 2D] FIG. 2 is a schematic diagram showing a state of a plating bath (solution) before entering a third stage of a reaction in the plating bath in the manufacturing method for a water electrolysis electrode according to the first embodiment, and a state of dendritic precipitates and an Fe-Ni-Sn double hydroxide on the surface of a conductive substrate. [Figure 2E] FIG. 3 is a schematic diagram illustrating a state in which the first and second stages are repeated as a third stage of a reaction in a plating bath (solution) in the method for producing a water electrolysis electrode according to the first embodiment. [Figure 2F] FIG. 4 is a schematic diagram illustrating a reaction state in a comparative example of the method for producing a water electrolysis electrode according to the first embodiment. [Diagram 3] 4 is a qualitative analysis chart showing the results of component analysis of each point on a cross section of the water electrolysis electrode according to the first embodiment, performed using an energy dispersive X-ray analyzer. [Figure 4] FIG. 4 is a flow chart showing a method for producing a water splitting electrode according to a second embodiment of the present invention. [Figure 5A] FIG. 11 is a schematic diagram showing a state after preparation of a plating bath (solution) in a method for producing an electrode for water electrolysis according to a second embodiment. [Figure 5B] FIG. 4 is a schematic diagram showing a first stage of a reaction in a plating bath (solution) in a method for producing a water electrolysis electrode according to a second embodiment. [Figure 5C] FIG. 11 is a schematic diagram showing a second stage of a reaction in a plating bath (solution) in a method for producing a water electrolysis electrode according to a second embodiment. [Figure 5D]FIG. 11 is a schematic diagram showing a state of a plating bath (solution) before entering a third stage of a reaction in the plating bath in the production method for a water electrolysis electrode according to the second embodiment, and a state of dendritic precipitates and an Fe-Ni-Co-Sn double hydroxide on the surface of a conductive substrate. [Figure 5E] FIG. 11 is a schematic diagram illustrating a state in which the first and second stages are repeated as a third stage of a reaction in a plating bath (solution) in a method for producing a water electrolysis electrode according to a second embodiment. [Figure 5F] FIG. 11 is a schematic diagram illustrating a reaction state in a comparative example of the method for producing a water electrolysis electrode according to the second embodiment. [Figure 6] 11 is a qualitative analysis chart showing the results of component analysis of each point on a cross section of a sample of the water electrolysis electrode according to the second embodiment, performed using an energy dispersive X-ray analyzer. [Figure 7] 1 is an SEM image (1800x) of dendritic precipitates on the surface of an electrode for water electrolysis in Example 3. [Figure 8] 1 is an SEM image (magnification: 4800) of columnar precipitates in the water electrolysis electrode in Example 9. [Figure 9] 1 is an SEM image (1800x) of dendritic precipitates on the surface of the electrode for water electrolysis in Example 13. [Figure 10] 1 is an SEM image (magnification: 4800) of columnar precipitates in the water electrolysis electrode of Example 17. [Figure 11] 1 is a graph showing the results of Linear Sweep Voltammetry (LSV) measurement for measuring hydrogen overvoltage of water electrolysis electrodes according to Examples and Comparative Examples. [Figure 12] 1 is a graph showing the results of Linear Sweep Voltammetry (LSV) measurement for measuring oxygen overvoltage of water electrolysis electrodes according to Examples and Comparative Examples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0019] <Water electrolysis electrode according to the first embodiment and its manufacturing method> A water electrolysis electrode and a method for producing the same according to a first embodiment of the present invention will be described below with reference to FIGS. 1 to 3. Fig. 1 is a flow diagram of the method for producing a water electrolysis electrode according to the first embodiment. Fig. 2A is a schematic diagram showing a step of preparing a plating bath (solution) used in the method for producing a water splitting electrode, Fig. 2B is a schematic diagram showing a first step of a reaction occurring in the plating solution, Fig. 2C is a schematic diagram showing a second step, and Figs. 2D and E are schematic diagrams showing a third step. In Fig. 1, step S1-1 is a pretreatment process for the conductive substrate. The conductive substrate used in this embodiment is preferably made of Ni, Ti (titanium), or carbon, which are corrosion-resistant even in an alkaline solution, but since the portion actually exposed to the solution is a film covering the conductive substrate surface, inexpensive materials such as Cu (copper), stainless steel, or Al (aluminum) may also be used. However, it is desirable for the conductive substrate to be mesh-shaped in order to efficiently separate gas bubbles generated during the reaction. As a pretreatment for the conductive substrate in step S1-1, a degreasing treatment and an activation treatment are performed. Specifically, for example, the degreasing process involves alkaline electrolytic degreasing for about one minute, with the aim of removing so-called contaminants such as oil from the surface of the substrate. The process involves placing the substrate to be treated on the cathode in an alkaline solution, placing a Pt or Ni plate on the anode, and applying a cathode current density of 20 to 50 [mA / cm 2 ] and electricity is applied for about one minute. The acid cleaning treatment involves immersing the substrate in hydrochloric acid containing ferric chloride to remove the oxide film formed on the substrate surface.

[0020] Step S1-2 is a process of disposing a precursor on a conductive substrate. Specifically, it is a process of immersing a conductive substrate in a plating bath (solution) as a wet film formation method. The plating bath composition is 0.01 to 0.1 [mol / dm 3 ] of NiCl2 (nickel chloride), 0.005 to 0.1 [mol / dm 3 ] of SnCl2 (tin chloride), 0.02 to 0.1 [mol / dm 3] of FeCl3 (iron chloride), 0.5 [mol / dm 3 ] of K2P2O7 (pyrophosphate), 0.1 [mol / dm 3 ]C2H5NO2 (glycine). FIG. 2A shows a schematic diagram of the plating bath and conductive substrate 1. For convenience, K2P2O7 and C2H5NO2 (glycine) are omitted from the plating bath, and only Ni ions 2, Sn ions 3, and Fe ions 4 are shown, showing the state in which the conductive substrate 1 is immersed in the plating solution. In this case, the equal sign written in the boxed area in the figure as the concentration of the plating bath does not mean that the concentrations of Ni ions 2, Sn ions 3, and Fe ions 4 are equal, but means that the balance of increases and decreases based on the prepared plating bath composition. Therefore, this figure means that the respective concentrations in the prepared plating bath composition are maintained. In addition, for example, an inequality that Fe ions 4 are more than Ni ions 2 and Sn ions 3 means that, when the prepared plating bath composition is used as a reference, the concentration of Fe ions 4 is less reduced from the concentration after preparation compared to the concentrations of Ni ions 2 and Sn ions 3, and is relatively more present compared to the concentration after preparation. The same applies to FIGS. 2B-2D, 2F, 5A-5D, and 5F.

[0021] Step S1-3 is the first stage of the reaction, and is a process of forming a composite film (hereinafter referred to as Fe-Ni-Sn composite film) as a first deposit on a conductive base material in order to construct a water electrolysis electrode according to the first embodiment. The plating bath conditions are a plating bath temperature of 50°C and pH of 8, adjusted using HCl (hydrochloric acid) and NaOH (sodium hydroxide). The electrolysis conditions are a current density of 40 to 2000 mA / cm 2 ] and plating is performed for 2 hours in combination with step S1-4 described later. In this manner, a Ni-Fe-Sn composite film is formed as a first deposit on the conductive substrate. FIG. 2B shows the state of the plating bath in the first stage of the reaction and a schematic diagram of an Fe-Ni-Sn composite film (dendritic deposit 6) formed as a first deposit in the form of dendrites on a conductive substrate 1. Here, the current density is set to 40 to 2000 [mA / cm2 ], Ni ions 2 and Sn ions 3 have equilibrium potentials of -0.25 [V] and -0.14 [V], respectively, which are small absolute values ​​and therefore easily reduced to metals, and so are first deposited on the conductive substrate 1. On the other hand, Fe ions 4 have an equilibrium potential of -0.44 [V], which is a large absolute value, so they hardly deposit at all, and then Ni ions 2 and Sn ions 3 deposit further on the convex parts of the initial deposit. This process is repeated to form a dendritic deposit 6. The deposition of Ni ions 2 and Sn ions 3 forms a concentration gradient of Ni ions 2 and Sn ions 3 from the dendritic deposit 6 to the solution. In other words, the concentration is low near the dendritic deposit 6 and high toward the bottom of the solution. Therefore, in the first stage of the reaction, the concentrations of Ni ions 2 and Sn ions 3 in the plating bath (solution) in the reaction region near the conductive substrate 1 are lower than the concentration of Fe ions 4 (see the description in the boxed area in the figure).

[0022] Here, in the method for producing a water splitting electrode according to the first embodiment, the plating current density is important in the immersion treatment in the plating bath in step S1-3. First, conventional electroplating is performed by directly reducing the target metal species at the cathode and depositing it on the surface, as shown in equation (1). M 2+ +2e - → M (1) Next, in the case of forming double hydroxides using conventional electroplating, if nitrate is used as the precursor of the metal species, the reaction shown in formula (2) occurs at the cathode, which is different from the above-mentioned normal plating, and the nitrate itself is reduced. At the same time, hydroxide ions (OH-) are generated and adsorbed to the cathode. No.3 - +H2O+2e - → NO2 - +2HO - (2) On the other hand, metal species are oxidized to higher metal species at the anode as shown in equation (3), and these are hydrolyzed at the cathode to produce double hydroxides. M 2+ → M (2+α)+ +αe- (3) In the manufacturing method of the water electrolysis electrode according to the present embodiment, the synthesis method is based on the direct reduction of metal species (formula (1)) using the principle of conventional electroplating. However, since electroplating is performed in a high current density zone, hydrogen is generated by electrolysis of water in addition to the reduction of metal species. At this time, the pH rises on the cathode surface, and double hydroxides such as hydroxides are formed. In applications such as antiseptic and decorative purposes, this is considered to be abnormal deposition accompanied by so-called "charring," but in the water electrolysis electrode according to the present embodiment, the reduction of metal species and the generation of double hydroxides such as oxides are important elements.

[0023] Next, step S1-4 is the second stage of the reaction, in which an Fe-Ni-Sn double hydroxide is directly formed as a second precipitate on the first precipitate and bonded to the first precipitate in order to form the water electrolysis electrode according to the first embodiment. The plating bath (solution) conditions are the same as those in step S1-3, and the electrolysis conditions are a current density of 40 to 2000 [mA / cm 2

[0113] Steps S1-3 and S1-4 are combined and plated for 2 hours. Note that steps S1-3 and S1-4 are consecutive processes, and step S1-4 is not started after step S1-3 is completed. Under these conditions, the second precipitate, an Fe-Ni-Sn double hydroxide, is directly bonded to the first precipitate. FIG. 2C shows a schematic diagram of the state of the plating bath in the second stage of the reaction and the formation of an Fe-Ni-Sn double hydroxide 7 as a second precipitate directly bonded to the dendritic precipitate 6 on the conductive substrate 1. The concentrations of Ni ions 2 and Sn ions 3 decreased in the first stage. When the absolute value of the parallel potential of Sn ions 3, which has the smallest absolute value, decreases, the Ni ions 2 remaining in the solution with a slow reduction rate and the Fe ions 4 that have hardly precipitated start to precipitate. At this time, the second precipitate, for example, Ni 1-x Fe x (OH) 2 etc., the Fe-Ni-Sn double hydroxide 7 is directly bonded onto the Fe-Ni-Sn composite film (dendritic precipitate 6). Compared to the first stage, in the Fe-Ni-Sn double hydroxide 7, Fe ions 4 in particular are produced in large quantities together with Ni ions 2 and Sn ions 3, and therefore the concentrations of Ni ions 2, Sn ions 3, and Fe ions 4 are all low in the reaction region in the vicinity of the conductive substrate 1 (see the description of the area enclosed in a square in the figure).

[0024] Then, the third stage of the reaction returns to step S1-3 again, and this time, instead of on the surface of the conductive substrate 1, a process of forming an Fe-Ni-Sn composite film as a first precipitate on the Fe-Ni-Sn composite film (dendritic precipitate 6) as a first precipitate formed on the conductive substrate 1 in the previous step S1-3, and then proceeds to step S1-4, where a process of forming an Fe-Ni-Sn double hydroxide 7 as a second precipitate on the added Fe-Ni-Sn composite film and directly bonding it is repeated. The plating bath conditions in the repetitive steps are not changed (the plating bath is not adjusted after step S1-1), and the electrolysis conditions are also the same as in steps S1-3 and S1-4. Figure 2D shows a schematic diagram of the state of the plating bath before entering the third stage of the reaction, and the state of the dendritic precipitate 6 and Fe-Ni-Sn double hydroxide 7 on the surface of the conductive substrate 1. Before entering the third stage, the Ni ions 2, Sn ions 3, and Fe ions 4 were all low in the second stage of the reaction (step S1-4), but since Ni ions 2, Sn ions 3, and Fe ions 4 are supplied by diffusion from offshore, where the solution concentration is high, the respective ion concentrations near the conductive substrate 1 have recovered to roughly the same level as in the state after the plating bath (solution) was adjusted. 2E shows the state of the plating bath after steps S1-3 and S1-4 have been repeated as the third stage of the reaction, and shows a state in which a film of dendritic precipitates 6 is formed in the gaps on the conductive substrate 1 where no Fe-Ni-Sn double hydroxide 7 has been formed, and further Fe-Ni-Sn double hydroxide 7 is directly bonded to the newly formed dendritic precipitates 6 (indicated by the dashed line in the figure). This third stage reaction is repeated until the supply of Ni ions 2, Sn ions 3, and Fe ions 4 from offshore of the plating bath runs out.

[0025] Next, FIG. 2F shows a comparative example for the first embodiment, in which the electrolysis conditions are a current density of 40 [mA / cm 2 ] is shown diagrammatically. As shown in Fig. 2F, when the current density was 40 mA / cm 2 2A, an Fe-Ni-Sn composite film (dendritic precipitate 6) is not formed as a first precipitate on the conductive substrate 1, and only a smooth Ni-Sn alloy 5 is formed on the conductive substrate 1. Moreover, an Fe-Ni-Sn double hydroxide 7 is not formed on the Ni-Sn alloy 5 thereafter.

[0026] Fig. 3 is a qualitative analysis chart showing the results of component analysis of each point on a cross section of the water electrolysis electrode according to the first embodiment using an energy dispersive X-ray analyzer. In Fig. 3, the horizontal axis indicates the energy level (KeV) when an analytical electron beam is applied to the sample and characteristic X-rays emitted from atoms contained in the sample are detected by a semiconductor detector, and the vertical axis indicates the intensity (count number) of the characteristic X-rays corresponding to the energy level (KeV), but since the intensity is shown for relative comparison, an arbitrary unit is used. The water electrolysis electrode according to the present embodiment has a unique structure in which a double hydroxide as a second precipitate is directly bonded to the surface of a dendritic or columnar precipitate as a first precipitate that is directly bonded to the surface of the conductive substrate. By showing the component analysis results at each analysis point, it is clear that a precipitate having a composition clearly different from that of the conductive substrate is formed on the surface. Furthermore, by analyzing each point in the precipitate, the dendritic or columnar precipitate and the double hydroxide can be clearly distinguished. Specifically, in the first embodiment, Ni was used as the conductive substrate 1, so the conductive substrate shown by the fine dashed line in the figure has a peak at the location of Ni. In addition, in the first precipitate shown by the larger dashed line, peaks are seen at the locations of Ni, Sn, and oxygen (O), but the Fe peak near 0.8 [KeV] on the horizontal axis is quite low, and no peak is detected near 6.4 [KeV]. Furthermore, in the second precipitate shown by the solid line, Fe peaks are detected at both 0.8 [KeV] and 6.4 [KeV] in addition to Ni, Sn, and oxygen. Therefore, it can be understood that the Fe-Ni-Sn composite film as the first precipitate contains almost no Fe, and that Ni and Sn are precipitated first in the plating bath, and then a large amount of Fe is also precipitated in the plating bath, and the Fe-Ni-Sn double hydroxide as the second precipitate contains a lot of Fe and is joined on top of the Fe-Ni-Sn composite film. That is, the Fe content (at %) in the Fe-Ni-Sn composite film (dendritic precipitate 6) which is the first precipitate is greater than the Fe content (at %) in the Fe-Ni-Sn double hydroxide 7 which is the second precipitate. This will also be shown in the Examples. In addition, Fe-Ni-Sn double hydroxides also include iron oxyhydroxide (FeOOH) and nickel oxyhydroxide (NiOOH).

[0027] <Water electrolysis electrode according to the second embodiment and its manufacturing method> Next, a water electrolysis electrode and a method for producing the same according to a second embodiment of the present invention will be described with reference to FIGS. Fig. 4 is a flow diagram of the method for producing a water electrolysis electrode according to the second embodiment. Fig. 5A is a schematic diagram showing a step of preparing a plating bath (solution) used in the method for producing a water splitting electrode, Fig. 5B is a schematic diagram showing a first step of a reaction occurring in the plating solution, Fig. 5C is a schematic diagram showing a second step, and Figs. 5D and E are schematic diagrams showing a schematic diagram showing a third step. In FIG. 4, step S2-1 is a pretreatment step for the conductive substrate, which is the same as in the first embodiment and will not be described.

[0028] Next, step S2-2 is a process of disposing a precursor on a conductive base material. Specifically, it is a process of immersing the conductive base material in a plating bath (solution) as a wet film formation method. The plating bath composition is the composition in the first embodiment with a difference of 0.005 to 0.1 [mol / dm 3 ] CoCl2 (cobalt chloride) is added. FIG. 5A shows a schematic diagram of the plating bath and the conductive substrate 1. For convenience, K2P2O7 and C2H5NO2 (glycine) are omitted from the plating bath, and only Ni ions 2, Sn ions 3, Fe ions 4, and Co ions 8 are shown, showing the state in which the conductive substrate 1 is immersed in the plating solution. At this time, as shown in the squared area in the figure, the concentrations of the Ni ions 2, Sn ions 3, Fe ions 4, and Co ions 8 in the plating bath are all roughly equal, although there are some differences in their shading. Note that the concentrations in the solution shown in the squared area indicate the local concentrations in the area reacting near the conductive substrate 1, as in the first embodiment.

[0029] Step S2-3 is the first stage of the reaction, in which a composite film (hereinafter referred to as Fe-Ni-Co-Sn composite film) is formed as a first deposit on a conductive base material to produce a water electrolysis electrode according to the second embodiment. The plating bath conditions and electrolysis conditions are the same as those in the first embodiment. 5B shows a schematic diagram of the state of the plating bath in the first stage of the reaction and the Fe-Ni-Co-Sn composite film (dendritic deposit 10) formed as a first deposit in a dendritic shape on the conductive substrate 1. Here, the equilibrium potential of the Co ions 8 will be explained. As described in the explanation of the first embodiment, the equilibrium potentials of the Ni ions 2 and Sn ions 3 are -0.25 [V vs. SHE (standard hydrogen electrode)] and -0.14 [V vs. SHE], respectively, and the absolute values ​​are small and they are easily reduced to metals. However, the Co ions 8 are also -0.28 [V vs. SHE], which is almost the same as the Ni ions 2, and is smaller in absolute value than the Fe ions 4, which have an absolute value of -0.44 [V vs. SHE]. Therefore, similarly to the first embodiment, Ni ions 2, Sn ions 3, and Co ions 8 are first precipitated on the conductive substrate 1, Fe ions 4 are hardly precipitated, and then Ni ions 2, Sn ions 3, and Co ions 8 are further precipitated on the convex parts of the initial precipitate, and this is repeated to form a dendritic precipitate 10. Then, due to the precipitation of Ni ions 2, Sn ions 3, and Co ions 8, a gradient of Ni ions 2, Sn ions 3, and Co ions 8 from low concentration to high concentration is formed from the dendritic precipitate 10 to the offshore of the solution part, similarly to the first embodiment. Therefore, in the first stage of the reaction, the concentrations of Ni ions 2, Sn ions 3, and Co ions 8 in the plating bath (solution) in the reaction region near the conductive substrate 1 are lower than the concentration of Fe ions 4 (see the description in the boxed area in the figure).

[0030] Next, step S2-4 is the second stage of the reaction, in which an Fe-Ni-Co-Sn double hydroxide is directly formed as a second precipitate on the first precipitate and bonded to the first precipitate to form a water electrolysis electrode according to the second embodiment. The plating bath (solution) conditions and electrolysis conditions are the same as those in step S1-3. In this manner, the Fe—Ni—Co—Sn double hydroxide 11 as the second precipitate is directly bonded to the first precipitate. FIG. 5C shows a schematic diagram of the state of the plating bath in the second stage of the reaction and the formation of an Fe—Ni—Co—Sn double hydroxide 11 as a second precipitate directly bonded to the dendritic precipitate 10 on the conductive substrate 1. The concentrations of Ni ions 2, Sn ions 3, and Co ions 8 decreased in the first stage. When the absolute value of the parallel potential of Sn ions 3, which has the smallest absolute value, decreases, Ni ions 2 and Co ions 8 remaining in the solution with a slow reduction rate and Fe ions 4 that have hardly precipitated start to precipitate. At this time, as the second precipitate, for example, Ni 1-x Fe x (OH) 2 etc., an Fe-Ni-Co-Sn double hydroxide 11 is directly bonded onto the Fe-Ni-Co-Sn composite film (dendritic precipitate 10). Compared to the first stage, in the Fe-Ni-Co-Sn double hydroxide 11, Fe ions 4 in particular are produced in large quantities together with Ni ions 2, Sn ions 3, and Co ions 8, so that in the reaction region near the conductive substrate 1, the concentrations of all of the Ni ions 2, Sn ions 3, Co ions 8, and Fe ions 4 become low (see the description of the area enclosed in a square in the figure).

[0031] Next, the third stage of the reaction returns to step S2-3 again, and this time, instead of on the surface of the conductive substrate 1, a process of forming an Fe-Ni-Co-Sn composite film as a first precipitate on the Fe-Ni-Co-Sn composite film (dendritic precipitate 10) as a first precipitate formed on the conductive substrate 1 in the previous step S2-3, and then proceeds to step S2-4, where a process of forming an Fe-Ni-Co-Sn double hydroxide 11 as a second precipitate on the added Fe-Ni-Co-Sn composite film and directly bonding it is repeated. The plating bath conditions in the repetitive steps are not changed (the plating bath is not adjusted after step S2-1), and the electrolysis conditions are also the same as in steps S2-3 and S2-4. Figure 5D shows a schematic diagram of the state of the plating bath before entering the third stage of the reaction, and the state of the dendritic precipitate 10 and Fe-Ni-Co-Sn double hydroxide 11 on the surface of the conductive substrate 1. Before entering the third stage, the Ni ions 2, Sn ions 3, Co ions 8, and Fe ions 4 were all low in the second stage of the reaction (step S2-4), but since Ni ions 2, Sn ions 3, Co ions 8, and Fe ions 4 are supplied by diffusion from offshore where the solution concentration is high, the respective ion concentrations near the conductive substrate 1 have recovered to roughly the same level as in the state after the plating bath (solution) was adjusted.

[0032] 5E shows the state of the plating bath after steps S2-3 and S2-4 are repeated as the third stage of the reaction, and shows a state in which dendritic precipitates 10 are further formed in the gaps on the conductive substrate 1 where no Fe-Ni-Co-Sn double hydroxides 11 have been formed, and further Fe-Ni-Co-Sn double hydroxides 11 are directly bonded to the newly formed dendritic precipitates 10 (indicated by the dashed line in the figure). This third stage reaction is repeated until there is no more supply of Ni ions 2, Sn ions 3, Co ions 8, and Fe ions 4 from the offshore of the plating bath.

[0033] Next, FIG. 5F shows a comparative example for the second embodiment, in which the electrolysis conditions are a current density of 40 [mA / cm 2 ] is shown diagrammatically. As shown in FIG. 5F, when the current density was 40 mA / cm 2 5A , an Fe-Ni-Co-Sn composite film (Fe-Ni-Co-Sn double hydroxide 11) is not formed as a first precipitate on the conductive substrate 1, and only a smooth Ni-Sn-Co alloy 9 is formed on the conductive substrate 1. Moreover, thereafter, the Fe-Ni-Co-Sn double hydroxide 11 is not formed on the Ni-Sn-Co alloy 9.

[0034] 6 is a qualitative analysis chart showing the results of component analysis of each point on a cross section of the water electrolysis electrode according to the second embodiment using an energy dispersive X-ray analyzer. The horizontal and vertical axes in FIG. 6 are the same as those in FIG. The electrode for water electrolysis according to the present embodiment also has a unique structure in which a double hydroxide as a second precipitate is directly bonded to the surface of a dendritic precipitate or a columnar precipitate as a first precipitate directly bonded to the surface of the conductive base material, and from this qualitative analysis chart, the dendritic or columnar precipitate and the double hydroxide can be clearly distinguished from the analysis of each point in the conductive base material and the precipitate. Specifically, since Ni was used as the conductive substrate 1 in the second embodiment, the conductive substrate shown by the fine dashed line in the figure has a peak at the location of Ni. In addition, in the first precipitate shown by the larger dashed line, peaks are seen at the locations of Ni, Sn, and oxygen (O), but a slight peak is also seen at the location of Co. It can also be seen that almost no peaks are detected near 6.4 [KeV] for Fe on the horizontal axis. Furthermore, in the second precipitate shown by the solid line, in addition to Ni, Sn, and oxygen (O), a peak for Fe is detected at 6.4 [KeV]. Therefore, it can be understood that the Fe-Ni-Co-Sn composite film as the first precipitate contains almost no Fe, that Ni, Sn, and Co are precipitated first in the plating bath, and that a large amount of Fe is then precipitated in the plating bath, and that the Fe-Ni-Co-Sn double hydroxide 11 as the second precipitate contains a large amount of Fe and is joined on top of the Fe-Ni-Co-Sn composite film. Therefore, also in the second embodiment, the Fe content (at %) in the Fe-Ni-Co-Sn composite film (dendritic precipitate 10) which is the first precipitate is greater than the Fe content (at %) in the Fe-Ni-Co-Sn double hydroxide 11 which is the second precipitate. This will be shown in the examples as in the first embodiment. In addition, Fe-Ni-Co-Sn double hydroxides also contain iron oxyhydroxide (FeOOH) and nickel oxyhydroxide (NiOOH).

[0035] <Examples of the water electrolysis electrode according to the first embodiment> Examples of the water electrolysis electrode according to the first embodiment will now be described. Table 1 shows the plating bath composition, plating bath temperature, plating bath pH, ​​whether the plating bath was stirred during the production of the water electrolysis electrodes of Examples 1 to 9, and the current density during electrodeposition. In these examples, the plating bath composition is composed of NiCl2, SnCl2, FeCl3, K2P2O7, and C2H5NO2, and does not contain CoCl2. The plating bath temperature is 50°C, the plating bath pH is 8, and the plating bath is not stirred in Examples 1 to 8, but is stirred in Example 9, which has the same plating bath composition as Example 3. The plating current density is as shown in the table. Examples 6 to 8 are tested using the same plating bath composition as Example 3, but with different plating current densities. These examples are examples in which electrodes for water electrolysis having excellent compositions for the first and second precipitates and thus exhibiting excellent electrode properties were defined based on the results of tests conducted by the inventors regarding the effects of the plating bath composition, whether or not the plating bath was stirred, and the range of current density during electrodeposition on the compositions of the first and second precipitates shown in Table 2 and the electrode properties of the water electrolysis electrodes shown in Table 3. Table 1 shows the plating bath conditions and electrolysis conditions used in these examples. Specifically, the plating bath conditions and electrolysis conditions are shown in Fig. 1 when explaining the manufacturing method of the water splitting electrode according to the first embodiment. The form of the first precipitate differs depending on whether the plating bath is stirred or not, which will be described later.

[0036] [Table 1]

[0037] Table 2 shows the compositions in at% of the Fe-Ni-Sn composite film (dendritic precipitate 6) which is the first precipitate and the Fe-Ni-Sn double hydroxide 7 which is the second precipitate in the water electrolysis electrodes of Examples 1 to 9, as well as the at% composition ratios of Fe and Ni in percentages. As described in the first embodiment, Table 2 shows that the Fe component (at%) contained in the second precipitate is greater than the Fe component (at%) contained in the first precipitate in all of Examples 1 to 8 without stirring and Example 9 with stirring. Here, Fig. 7 shows an SEM image (1800x magnification) of dendritic precipitates on the surface of the water electrolysis electrode prepared in Example 3. This SEM image was taken, like other SEM images, of a cross-sectional sample, and all of the component analyses described above were carried out on these cross-sectional samples. A cross-sectional sample of the water electrolysis electrode prepared as an example was prepared, and the components of the first and second precipitates were analyzed using an EDX (JEOL JED-2300F) attached to a FE-SEM (JEOL JSM-7000F) at an accelerating voltage of 10 [keV] and a probe current of 0.2 [nA]. The average value of 10 measurement points was used. The cross-sectional sample was prepared by performing ion milling for 8 [h] at an accelerating voltage of 5.5 [keV] using a cross-section polisher (JEOL IB-09020CP). As shown in FIG. 7, it can be seen that a first precipitate, an Fe-Ni-Sn composite film (dendritic precipitate 6), is formed on the conductive substrate, and a second precipitate, an Fe-Ni-Sn double hydroxide, is deposited to cover the first precipitate or in the gaps between the first precipitate. FIG. 8 shows an SEM image (magnification: 4,300) of columnar precipitates on the surface of the electrode for water electrolysis produced in Example 9, in which the plating bath composition and electrolysis conditions were the same as those in Example 3, but the stirring of the plating bath was different. As can be seen in Figure 8, a first precipitate, an Fe-Ni-Sn composite film, is formed on the conductive substrate, and a second precipitate, an Fe-Ni-Sn double hydroxide, is deposited to cover the first precipitate or in the gaps between the first precipitate. However, the morphology of the first precipitate is particularly different, being thicker and firmer columns rather than dendritic. Without stirring, fluctuations occur in the concentration of Sn, which has a fast reduction rate, near the first precipitate. This means that electrodeposition occurs under diffusion-limited conditions, where the supply of ions is the rate-limiting factor for the reaction, and a dendritic structure is formed. On the other hand, with stirring, the supply of Sn ions is guaranteed compared to when there is no stirring. This means that electrodeposition occurs under conditions closer to activation-limited conditions, and it is thought that a denser columnar structure is formed compared to a dendritic structure.

[0038] [Table 2]

[0039] Table 3 shows the electrode characteristics (oxygen overvoltage, hydrogen overvoltage, durability upon anodic polarization, and ECSA) of the water electrolysis electrodes of Examples 1 to 8. Note that ECSA is different from the physical surface area calculated by the BET method (a surface area measurement method based on the BET adsorption isotherm), and refers to the electrochemical effective surface area of ​​the reaction field in the electrode where an electrochemical reaction can take place in solution. We will now explain the performance evaluation method shown in Table 3. Electrochemical measurements were carried out using a potentiogalvanostat (Toyo Corporation, SP-300). The evaluation items were linear sweep voltammetry to measure overpotential, and chronopotentiometry to evaluate durability. The electrochemical effective surface area was determined by cyclic voltammetry. Mercury (Hg) / HgO electrodes and platinum (Pt) wires were used for the electrodes produced in Examples 1 to 8 and all other Examples and Comparative Examples. The electrolyte was 1.0 [mol / dm 3 ] was used as a potassium hydroxide (KOH) solution. [Overvoltage measurement method] Linear sweep voltammetry was performed by controlling the potential from the open circuit potential at a sweep rate of 10 mV / s. The oxygen overpotential was controlled to the noble side at a current density of 100 mA / cm. 2 The hydrogen overvoltage was calculated by subtracting 1.23 [V] (theoretical potential for oxygen generation) from the potential required to reach the theoretical potential for hydrogen generation of 0 [V]. The hydrogen overvoltage was calculated by controlling the potential to the negative side, and because the theoretical potential for hydrogen generation is 0 [V], the hydrogen overvoltage was calculated by subtracting 1.23 [V] (theoretical potential for oxygen generation) from the potential required to reach the theoretical potential for hydrogen generation of 0 [V]. 2 The potential value required to reach [ [Durability evaluation method] Current density +600 [mA / cm 2 ] and recorded the change in potential over time by chronopotentiometry. When the electrocatalyst falls off or becomes inactive, a sudden increase in potential is observed, so the time required for this to happen was defined as the durability time [h]. [Method of measuring electrochemical effective surface area (ECSA)] The electrochemical effective surface area is the electric double layer capacity C dl The calculation was based on C dl The response current was measured by cyclic voltammetry at a sweep rate of 2-10 mV / s in the potential range of 0-0.1 V (vs. Hg / HgO). The sweep rate and electrochemically effective surface area (ECSA) were calculated using the following equation (4). ECSA=C dl / C s (4) Here, C s is the specific capacitance, 1.0 [mol / dm 3 ] in a KOH solution of 0.04 [mF / cm 2 The calculated electrochemical effective surface area was normalized by the amount of each catalyst.

[0040] [Table 3]

[0041] As shown in Table 3, all of Examples 1 to 8 exhibit excellent overvoltage characteristics, with oxygen overvoltages of 270 to 276 [mA] and hydrogen overvoltages of 169 to 176 [mA]. ​​In addition, the endurance time was also excellent, with a range of 154 to 165 [h]. Furthermore, the ECSA is 1.1 to 2.6 [m 2 / g], providing a sufficient surface area. Moreover, in Example 9, the hydrogen overvoltage was 162 [mA], which is superior to any of Examples 1 to 8. Other electrode properties were also within the ranges of the electrode properties of Examples 1 to 8, and it can be seen that Example 9 is equivalent to or superior to Examples 1 to 8.

[0042] <Examples of water electrolysis electrode according to the second embodiment> Examples of the water electrolysis electrode according to the second embodiment will now be described. Table 4 shows a summary of the plating bath composition, plating bath temperature, plating bath pH, ​​whether the plating bath was stirred during the production of the water electrolysis electrodes of Examples 10 to 17, and the current density during electrodeposition. In these examples, the plating bath composition is composed of NiCl2, CoCl2, SnCl2, FeCl3, K2P2O7, and C2H5NO2, the plating bath temperature is 50°C, the plating bath pH is 8, the plating bath is not stirred in Examples 10 to 16, and is stirred only in Example 17, which has the same plating bath composition as Example 13. The plating current density is as shown in the table. Also, Examples 14 to 16 are tested with the same plating bath composition as Example 13, but with different plating current densities. As in Examples 1 to 9, these Examples are examples in which the inventors conducted tests to determine how the plating bath composition, whether or not the plating bath was stirred, and the range of current density during electrodeposition affected the compositions of the first and second precipitates shown in Table 5 and the electrode properties of the water electrolysis electrode shown in Table 6, and determined that the electrodes had excellent compositions for the first and second precipitates and, as a result, exhibited excellent electrode properties. Table 4 shows the plating bath conditions and electrolysis conditions used in these tests. Specifically, the plating bath conditions and electrolysis conditions are shown in Fig. 4 when explaining the manufacturing method of the water splitting electrode according to the second embodiment, but are the same as the plating conditions and electrolysis conditions shown in the first embodiment except for the concentration of CoCl2 in the plating bath composition that is added. Note that, as in the examples according to the first embodiment, the form of the first precipitate differs depending on whether the plating bath is stirred or not, but this point will be described later.

[0043] [Table 4]

[0044] [Table 5]

[0045] Table 5 shows the compositions in at% of the Fe-Ni-Co-Sn composite film (dendritic precipitate 10) which is the first precipitate and the Fe-Ni-Co-Sn double hydroxide 11 which is the second precipitate in the water electrolysis electrodes of Examples 10 to 17, and also shows the at% composition ratios of Fe and Ni in percentages. As described in the first embodiment, Table 5 shows that the Fe component (at%) contained in the second precipitate is greater than the Fe component (at%) contained in the first precipitate in all of Examples 1 to 8 without stirring and Example 9 with stirring. FIG. 9 shows an SEM image (1800x) of dendritic precipitates on the surface of the water electrolysis electrode prepared in Example 13. As shown in FIG. 9, it can be seen that a first precipitate, an Fe-Ni-Co-Sn composite film (dendritic precipitate 10), is formed on the conductive substrate, and a second precipitate, an Fe-Ni-Co-Sn double hydroxide, is deposited to cover the first precipitate or in the gaps between the first precipitate. FIG. 10 shows an SEM image (magnification: 4,300) of columnar precipitates on the surface of the electrode for water electrolysis produced in Example 17 in which the plating bath composition and electrolysis conditions were the same as those in Example 3, but the stirring of the plating bath was different. In Fig. 10, it is observed that a first precipitate, an Fe-Ni-Co-Sn composite film, is formed on the conductive substrate, and a second precipitate, an Fe-Ni-Co-Sn double hydroxide, is deposited to cover the first precipitate or in the gaps between the first precipitate. However, as in Example 9, the morphology of the first precipitate is different, and it is thicker and firmer in the form of columns rather than in the form of dendrites. Furthermore, it appears to have a morphology very similar to that in Fig. 8. The reason for the columnar formation is as explained in Example 9.

[0046] Table 6 shows the electrode characteristics (oxygen overvoltage, hydrogen overvoltage, durability upon anodic polarization, and ECSA) of the water electrolysis electrodes of Examples 10 to 17. As shown in Table 6, all of Examples 10 to 17 exhibited excellent overvoltage characteristics, with oxygen overvoltages of 278 to 300 [mA] and hydrogen overvoltages of 162 to 189 [mA]. ​​In addition, the endurance time was also excellent, with a range of 161 to 315 [h]. Furthermore, the ECSA was 1.1 to 2.3 [m 2 / g], providing a sufficient surface area. In Example 17, the hydrogen overvoltage was 184 [mA], which was larger than that of Example 9 in which the plating bath was stirred, and the durability was shorter than that of Examples 10 to 17, so that it cannot be said that stirring the plating bath necessarily improves the electrode characteristics. It was also found that the durability of Examples 10 to 16 relating to the second embodiment was slightly longer than that of the examples relating to the first embodiment, and it was also found that the inclusion of Co in the plating bath improves the durability of the water electrolysis electrodes.

[0047] [Table 6]

[0048] <Effect of substrate of electrodes for water electrolysis according to the first and second embodiments> Next, examples in which the conductive substrate of the water electrolysis electrodes according to the first and second embodiments is changed will be described. The plating bath conditions and electrolysis conditions were the same as those of Example 2 of the first embodiment, but only the substrate was changed to carbon, Cu, Ti, stainless steel, and Al, resulting in Examples 18 to 22. The plating bath conditions and electrolysis conditions were the same as those of Example 3, but only the substrate was changed to carbon, Cu, Ti, stainless steel, and Al, resulting in Examples 23 to 27. The plating bath conditions and electrolysis conditions were the same as those of Example 11 of the second embodiment, but only the substrate was changed to carbon, Cu, Ti, stainless steel, and Al, resulting in Examples 28 to 32. The plating bath conditions and electrolysis conditions were the same as those of Example 12, but only the substrate was changed to carbon, Cu, Ti, stainless steel, and Al, resulting in Examples 33 to 37. Table 7 shows the plating bath composition, plating bath temperature, plating bath pH, ​​whether the plating bath was stirred during the production of the water electrolysis electrodes, and the current density during electrodeposition for these examples. The substrate is not shown in each example, but is shown in Tables 8 and 9. In these examples, the degreasing and acid cleaning treatments shown in Figures 1 and 4 were also performed. Specifically, the degreasing treatment was alkaline electrolytic degreasing for about 1 minute, and the purpose of this treatment was to remove so-called contaminants such as oil from the substrate surface. The treatment consisted of placing the substrate to be treated on the cathode in an alkaline solution, placing a Pt or Ni plate on the anode, and applying a cathode current density of 20 to 50 [mA / cm 2 ] and electricity is applied for about one minute. The acid cleaning treatment was carried out by immersing the substrate in hydrochloric acid containing ferric chloride to remove the oxide film formed on the substrate surface. In addition, for all other elements, NiSO4 was added at 0.15 [mol / dm 3 ], NaH2PO2 is 0.2 [mol / dm 3 ], C2H3NaO2 is 0.1 [mol / dm 3 ], Na3C6H5O7 is 0.04 [mol / dm 3 The electroless plating bath containing the composition: is controlled at 90°C and the substrate is immersed in the bath for 30 minutes. Thereafter, electrodeposition was carried out using the plating bath shown in Table 7.

[0049] [Table 7]

[0050] Table 8 shows the compositions in at% of the first precipitate (Fe-Ni-Sn composite film or Fe-Ni-Co-Sn composite film) and the second precipitate (Fe-Ni-Sn double hydroxide or Fe-Ni-Co-Sn double hydroxide) in the water electrolysis electrodes of Examples 18 to 37, and also shows the at composition ratios of Fe and Ni in percentage. The column for substrate in Table 8 shows the material (element) of the conductive substrate of the water electrolysis electrode, where C means carbon and S means stainless steel. It is clear from Table 8 that in all of these Examples, the Fe component (at %) contained in the second precipitates was greater than the Fe component (at %) contained in the first precipitates. Furthermore, even though the conductive base material was changed from Ni, the compositions of the first and second precipitates in Examples 18 to 22 were generally the same as the composition of Example 2. Similarly, the compositions of Examples 23 to 27, Examples 28 to 32, and Examples 33 to 37 were also generally the same as the compositions of Example 3, Example 11, and Example 12, respectively. Thus, even if the conductive base material is changed from Ni to carbon, Cu, Ti, stainless steel, or Al, water electrolysis electrodes having equivalent compositions can be obtained.

[0051] [Table 8]

[0052] Table 9 shows the electrode characteristics (oxygen overvoltage, hydrogen overvoltage, durability upon anodic polarization, and ECSA) of the water electrolysis electrodes of Examples 18 to 37. As can be seen from Table 9, the oxygen overvoltage and hydrogen overvoltage characteristics in all of Examples 18 to 37 are roughly equivalent to those in the case where the substrate is Ni. On the other hand, in terms of durability, Cu can be said to be roughly equivalent to when the base material is Ni, but for other materials (carbon, Ti, stainless steel, Al), while equivalent performance is exhibited in Examples 23 to 27, which are under the same conditions as Example 3, the durability was reduced to about 1 / 4 in Examples 2, 11, and 12, which are under the same conditions. It was found that the ECSA was comparable to that of Examples 2, 3, 11, and 12, all of which used Ni as the substrate. Therefore, it is considered possible to obtain a water electrolysis electrode exhibiting roughly equivalent electrode properties even if the conductive base material is changed from Ni to Cu. However, it was found that water electrolysis electrodes made of other materials may be inferior in terms of durability depending on the plating bath conditions and electrolysis conditions. It was also found that by using Ni or Cu as the conductive substrate, it is possible to manufacture a water electrolysis electrode that can exhibit stable and excellent electrode properties under plating bath conditions and electrolysis conditions.

[0053] [Table 9]

[0054] <Comparative Example> Next, tests were carried out on comparative examples in comparison with the examples, and the results are described below. Ni was used as the conductive substrate for the water electrolysis electrode in the comparative example. Table 10 summarizes the plating bath composition, plating bath temperature, plating bath pH, ​​whether or not the plating bath was stirred during the production of the water electrolysis electrodes, and the current density during electrodeposition for these comparative examples. These comparative examples are examples that deviate from the examples defined as water electrolysis electrodes having excellent compositions for the first and second precipitates and thus exhibiting excellent electrode properties, based on the results of tests conducted by the inventors regarding the effects of the plating bath composition, whether or not the plating bath is stirred, and the range of current density during electrodeposition on the compositions of the first and second precipitates and the electrode properties of the water electrolysis electrode. Table 10 shows the plating bath conditions and electrolysis conditions used in these comparative examples.

[0055] [Table 10]

[0056] Table 11 shows the compositions in at% of the first precipitate (Fe-Ni-Sn composite film or Fe-Ni-Co-Sn composite film) and the second precipitate (Fe-Ni-Sn double hydroxide or Fe-Ni-Co-Sn double hydroxide) in the water electrolysis electrodes of Comparative Examples 1 to 13, as well as the at% composition ratios of Fe and Ni in percentages. Note that in Comparative Examples 7 to 13, the second precipitate was not formed, so the fields are left blank. In Comparative Examples 7 to 13, as shown in Table 10, the current density during electrodeposition was 10 [mA / cm 2 This is thought to be due to the fact that the current density must be at least 40 mA / cm 2 ] was found to be necessary.

[0057] [Table 11]

[0058] Table 12 shows the electrode characteristics (oxygen overvoltage, hydrogen overvoltage, durability upon anodic polarization, and ECSA) of the water electrolysis electrodes of Comparative Examples 1 to 13. From Table 12, it can be seen that all of the electrode properties of oxygen overvoltage, hydrogen overvoltage, and endurance time in Comparative Examples 1 to 13 are lower than those in Examples 1 to 17, which use Ni as a conductive substrate. On the other hand, it can be seen that, although there are some Comparative Examples that are slightly higher in ECSA, most of them are lower, including the Comparative Example in which the second precipitate was not formed.

[0059] [Table 12]

[0060] Therefore, the hydrogen overvoltage and oxygen overvoltage of the electrode characteristics of the embodiment and the comparative example were compared. Fig. 11 is a graph showing the results of LSV (Linear Sweep Voltammetry) measurement for measuring hydrogen overvoltage of the water electrolysis electrodes according to the examples and the comparative examples, and Fig. 12 is a graph showing the results of LSV (Linear Sweep Voltammetry) measurement for measuring oxygen overvoltage. The hydrogen overvoltage was measured by controlling the potential to the negative side, and since the theoretical potential for hydrogen generation is 0 [V], the current density was 100 [mA / cm 2 The potential required to reach the threshold was used. The oxygen overvoltage was measured at a current density of 10 mA / cm 2 ] is the potential required to reach 100 The calculation was made using E(RHE)-1.23 [V] (theoretical potential for oxygen evolution). Both Fig. 11 and Fig. 12 compare the characteristics of the water electrolysis electrodes in Examples 3, 9, 13, 17, 19, and 29 with those in Comparative Examples 7 and 8. It can be seen from these figures that the characteristics of the Examples are clearly superior to those of the Comparative Examples. It can also be seen from Fig. 11 that there is almost no difference between these Examples, and that all of them clearly exhibit excellent effects.

[0061] Finally, we compared the catalyst with a precious metal (iridium: Ir) catalyst, and we will explain the results. The precious metal (Ir) catalyst was prepared by hydrothermal synthesis. First, 1.0[g] of carbon black and 1.5[g] of urea were thoroughly mixed. After washing with ethanol three times, the obtained black solid was transferred to a 60[℃] oven and left overnight. 1.0[g] of the dried sample was mixed with 2.0[g] of urea and baked at a low temperature of 175[℃] for 4 hours, after which the washing and drying process was repeated. The obtained black solid was stored in a glass vial. 75 mg of the black solid, 150 mg of ascorbic acid, 20 mL of ethylene glycol, and 16 mg of hexachloroiridate hydrate were added to a 50 mL vial, and the colloidal product was then washed three times with ethanol and placed in a vacuum drying oven at 60°C for 24 hours. The following procedure was followed for electrochemical measurements. 2.0 mg of sample, 800 μL of ethanol, and 8 μL of Nafion solution were dispersed by ultrasonic waves to form a uniform suspension. Then, 25 μL of the suspension was dispersed on a Ni substrate. This was used as the working electrode. In this manner, the durability of the Ni-based water electrolysis electrodes and Ir catalyst-coated electrodes according to Examples 1 to 9 was tested using 1 M potassium hydroxide (KOH) at 25°C and 30 weight % (wt%) KOH at 85°C, and the results are shown in Table 13. As shown in Table 13, it was found that there was no problem with durability in Examples 1 to 9. On the other hand, as shown in the table, the Ir catalyst-coated electrode was deactivated after 720 hours of anodic polarization in 1 M KOH at 25°C, and after 30 minutes of anodic polarization in 30 wt% KOH at 85°C. From the above results, it was understood that the electrode exhibited superior performance in terms of durability compared to the electrode coated with a precious metal catalyst (Ir).

[0062] [Table 13]

[0063] As described above, it has been found that a water electrolysis electrode having a structure in which a first precipitate in which Ni is combined with Sn and Fe, or a first precipitate in which Co is added to the first precipitate, is directly bonded to the surface of a conductive base material made of any one of Ni, Cu, carbon, Ti, stainless steel, or Al, and a second precipitate which is a double hydroxide, is directly bonded to the surface of the first precipitate, even though the electrode is a non-precious metal electrode which is inexpensive in terms of material and production costs. In other words, the electrode has extremely advantageous effects in that it has high catalytic activity, including high hydrogen overvoltage and oxygen overvoltage, and has high durability which enables the high catalytic activity to be maintained for a long period of time, even though the electrode is made of a non-precious metal which has low material and production costs. It was also found that the manufacturing method of the present invention for producing electrodes for electrolysis has the excellent effect of making it possible to manufacture non-precious metal electrodes for water electrolysis which have high catalytic activity and durability, and which are inexpensive in terms of materials and manufacturing costs. [Industrial Applicability]

[0064] The present invention can be widely used as an electrode for water electrolysis and an electrode for a fuel cell, and as a method for producing the same. [Explanation of symbols]

[0065] 1...Conductive substrate 2...Ni ion 3...Sn ion 4...Fe ion 5...Ni-Sn alloy 6...Dendritic precipitate 7...Fe-Ni-Sn double hydroxide 8...Co ion 9...Ni-Sn-Co alloy 10...Dendritic precipitate 11...Fe-Ni-Co-Sn double hydroxide

Claims

1. 1. An electrode for water electrolysis comprising: a first precipitate, in which Ni is combined with Sn and Fe, formed on a surface of a conductive base material; and a second precipitate, which is a double hydroxide, directly bonded to the surface of the first precipitate.

2. The electrode for water electrolysis according to claim 1, wherein the first precipitate has a composition in which Sn is 0.8 to 77 at% and a Fe / Ni ratio is in the range of 0.01 to 4 at% when the total of Ni, Sn, and Fe is taken as 100 at% (atomic %).

3. The electrode for water electrolysis according to claim 2, wherein the second precipitate has a composition in which, when the total of Ni, Sn, Fe, and oxygen is taken as 100 at % (atomic %), Sn is in the range of 0.1 to 33 at %, an Fe / Ni ratio is in the range of 9.93 to 49.19 at %, and oxygen is in the range of 5 to 49 at %.

4. 2. The electrode for water electrolysis according to claim 1, wherein the first precipitate comprises Ni complexed with Co in addition to Sn and Fe.

5. The electrode for water electrolysis according to claim 4, wherein a composition of the first precipitate is such that, when the total of Ni, Sn, Co, and Fe is taken as 100 at % (atomic %), Sn is in the range of 0.8 to 77 at %, Co is in the range of 0 to 23 at % (excluding 0), and an Fe / Ni ratio is in the range of 0.01 to 4 at %.

6. The electrode for water electrolysis according to claim 5, wherein the second precipitate has a composition in which, when the total of Ni, Sn, Co, Fe, and oxygen is taken as 100 at % (atomic %), Sn is in the range of 0.1 to 33 at %, Co is in the range of 0 to 70 at % (excluding 0), an Fe / Ni ratio is in the range of 9.93 to 49.19 at %, and oxygen is in the range of 5 to 49 at %.

7. 7. The electrode for water electrolysis according to claim 1, wherein the conductive base material is made of any one of Al, Ni, carbon, Cu, Ti, and stainless steel.

8. The electrode for water electrolysis according to any one of claims 1 to 6, wherein the first precipitate has a dendritic structure or a columnar structure in which columnar secondary arms serving as side branches grow in irregular directions from a columnar primary arm serving as a main trunk.

9. At least NiCl is deposited on a conductive substrate as a precursor. 2 , SnCl 2 and FeCl 3 disposing a chloride salt comprising: a first film-forming step of precipitating a first precipitate in which Ni is combined with at least Sn and Fe by the wet film-forming method; a second film-forming step of directly bonding a second precipitate, which is a double hydroxide, to a surface of the first precipitate by the wet film-forming method; In the first and second film-forming steps, the plating bath temperature is 50° C., the pH is 8, and the plating current density is 40 to 2000 mA / cm 2 The method of claim 1, further comprising controlling the temperature of the electrode for water electrolysis to the temperature above 100° C.

Citation Information

Patent Citations

  • Soluble electrode catalyst

    JP2013117041A